Analysis of Dynamic Systems

Schedule:

  • Getting started
  • Introduction
  • Mathematical bases
  • Bode diagrams
  • Modeling with linear elements
  • State variables
  • Block diagrams
  • Time response
  • Frequency response
  • Stability
  • Root Locus
  • Final project
  • Course evaluation

Mathematical bases

  • Complex Variable Theory.
  • Differential equations.
  • Laplace transform.
  • Theory of matrices.
  • Bode diagrams.

In [ ]:
import sympy
from sympy import *
sympy.init_printing()
s = Symbol('s')
t = Symbol('t', positive=True)

Laplace transform

Tool for the solution of linear differential equations.

Definition: For a function $f(t)$ such that:

$$\int_{0}^{\infty }\left | f(t) \, e^{\sigma t} \right | dt< \infty$$

For a finite real value of $\sigma$, the Laplace transform of $f(t)$ is defined as:

$$F\left ( s \right ) = \int_{0}^{\infty } f\left ( t \right ) \, e^{-st} dt$$

This is the unilateral Laplace transform. Or:

$$F\left ( s \right ) = \mathfrak{L} \left [ f\left ( t \right ) \right ]$$
  • The variable $s$ is known as the Laplace operator, and is a complex variable.
  • All the information contained in $f(t)$ prior to $t = 0$ is ignored or considered equal to zero, this does not normally affect calculations since the time reference that is normally used is $t = 0$.
  • We will not use the definition of the Laplace transform, but the tables of the books.

In [ ]:
from IPython.display import Image
Image(filename='img/laplace_fig1.png')

Example: Consider a unitary step function $f(t)$:


In [ ]:
import numpy as np
import matplotlib.pyplot as plt

x = [-1, 0, 0, 1, 2, 3]
y = [0, 0, 1, 1, 1, 1]

plt.plot(x, y, 'r', label='f(t) = u(t)', linewidth=3)
plt.title('Unitary step function')
plt.xlabel('t')
plt.ylabel('f(t)')
plt.legend()
plt.xlim(-1, 3)
plt.ylim(-1, 2)
plt.grid()
plt.show()
$$F\left ( s \right ) = \mathfrak{L}\left [ u\left ( t \right ) \right ] = \int_{0}^{\infty } u\left ( t \right ) e^{-st} dt$$
$$\Rightarrow \, F\left ( s \right ) = \left [ - \frac{1}{s} e^{-st} \right ] _{0}^{\infty } = \frac{1}{s}$$

Inverse of Laplace Transforms

It seeks to obtain $f(t)$ from $F(s)$.

$$f\left ( t \right ) = \boldsymbol{\mathfrak{L}}^{-1} \left [ F\left ( s \right ) \right ]$$
$$f\left ( t \right ) = \frac{1}{2\pi j} \int_{c-j\infty }^{c+j\infty } F\left ( s \right ) e^{st} ds$$

Theorems

1. Multiplication by a constant

$$\boldsymbol{\mathfrak{L}} \left [ k \, f \left (t \right ) \right ] = k \, F \left (s \right )$$

2. add and subtract

$$\mathfrak{L} \left [ f_1 \left ( t \right ) \pm f_2 \left ( t \right ) \right ] = F_1 \left ( s \right ) \pm F_2 \left ( s \right )$$

3. Differentiation

$$\mathfrak{L} \left [ \frac{d\, f\left ( t \right )}{dt} \right ] = s \, F\left ( s \right ) - \lim_{t \to 0} f\left ( t \right ) = s \, F\left ( s \right ) - f\left ( 0 \right )$$
$$\mathfrak{L} \left [ \frac{d^n \, f\left ( t \right )}{dt^n} \right ] = s^n \, F\left ( s \right ) - \lim_{t \to 0} \left [ s^{n-1} f\left ( t \right ) + s^{n-2} \frac{df\left ( t \right )}{dt} + \cdots +s^{0} \frac{d^{n-1} f\left ( t \right )}{dt^{n-1}} \right ]$$
$$\mathfrak{L} \left [ \frac{d^n \, f\left ( t \right )}{dt^n} \right ] = s^n \, F\left ( s \right ) - s^{n-1} f\left ( 0 \right ) - s^{n-2} f^{\left ( 1 \right )} - \cdots - f^{\left ( n-1 \right )} \left ( 0 \right )$$

4. Integration

$$\mathfrak{L} \left [ \int_{0}^{t} f\left ( \tau \right ) d\tau \right ] = \frac{F\left ( s \right )}{s}$$
$$\mathfrak{L} \left [ \int_{0}^{t_1} \int_{0}^{t_2} \cdots \int_{0}^{t_n} f\left ( \tau \right ) d\tau \, dt_1 \cdots dt_{n-1}\right ] = \frac{F\left ( s \right )}{s^n}$$

5. Time shift

$$\mathfrak{L} \left [ f\left ( t-T \right ) u\left ( t-T \right )\right ] = e^{-Ts} F\left ( s \right )$$

Where $u\left ( t-T \right )$ is the unitary step offset to the right.

6. Initial value theorem

$$\lim _{t \to 0} f\left ( t \right ) = \lim _{s \to \infty } sF\left ( s \right )$$

7. Final value theorem

$$\lim _{t \to \infty} f\left ( t \right ) = \lim _{s \to 0 } sF\left ( s \right )$$

If and only if $F(s)$ is analytic in the imaginary axis and in the right half-plane of $s$.

Example: Consider the function $F_1(s)$:

$$F_1\left ( s \right ) = \frac{5}{s\left ( s^2 + s + 2 \right )}$$

The poles of $F_1(s)$ are:


In [ ]:
F1 = 5/(s*(s**2+s+2))
F1.expand()

In [ ]:
from control import *
from scipy import signal

sysF1 = signal.lti([5], [1, 1, 2, 0]) # F1(s) = (5) / (s *** 3 + s ** 2 + 2 * s + 0)
w, H = signal.freqresp(sysF1)
print(sysF1.zeros, sysF1.poles, sysF1.gain)

In [ ]:
plt.plot(sysF1.zeros.real, sysF1.zeros.imag, 'o')
plt.plot(sysF1.poles.real, sysF1.poles.imag, 'x')
plt.title('Poles and Zeros')
plt.xlabel('Re')
plt.ylabel('Im')
plt.xlim(-3, 3)
plt.ylim(-3, 3)
plt.grid()
plt.show()
$$0, \, -\frac{1}{2} \pm j\frac{\sqrt{7}}{2}$$

Since the function is analytic on the imaginary axis and on the right half-plane of $s$, then it fulfills the final value theorem. Thus:

$$\lim _{t \to \infty } f\left ( t \right ) = \lim _{s \to 0 } s F\left ( s \right ) = \lim _{s \to 0 } \frac{5}{s^2+s+2} = \frac{5}{2}$$
$$ \Rightarrow \lim _{t \to \infty } f\left ( t \right ) = \frac{5}{2} $$

Example: Consider the function $F_2(s)$:

$$ F_2 \left ( s \right ) = \frac{\omega }{s^2 + \omega ^2} $$

And we know that $f_2 \left ( t \right ) = sin \left ( \omega t \right )$. The poles are: $\pm j \omega $

$ \Rightarrow $ Does not meet the final value theorem

$ \Rightarrow $ We can not determine the final value of $f(t)$.

8. Complex displacement

$$\mathfrak{L} \left [ e^{\mp at} f\left ( t \right ) \right ] = F \left ( s \pm a \right )$$

9. Real convolution (complex multiplication)

$$F_1 \left ( s \right ) F_2 \left ( s \right ) = \mathfrak{L} \left [ \int_{0}^{t} f_1 \left ( \tau \right ) f_2 \left ( t - \tau \right ) d\tau \right ]$$
$$F_1 \left ( s \right ) F_2 \left ( s \right ) = \mathfrak{L} \left [ \int_{0}^{t} f_2 \left ( \tau \right ) f_1 \left ( t - \tau \right ) d\tau \right ]$$
$$ F_1 \left ( s \right ) F_2 \left ( s \right ) = \mathfrak{L} \left [ f_1 \left ( t \right ) * f_2 \left ( t \right ) \right ] $$

Note: $\mathfrak{L}^{-1} \left [ F_1 \left ( s \right ) F_2 \left ( s \right ) \right ] \neq f_1 \left ( t \right ) \, f_2 \left ( t \right ) $

10. Complex convolution (real multiplication)

$$\mathfrak{L} \left [ f_1 \left ( t \right ) f_2 \left ( t \right ) \right ] = F_1 \left ( s \right ) * F_2 \left ( s \right )$$

Partial fractions

1. Simple poles

$$ X \left ( s \right ) = \frac{P \left ( s \right )}{Q \left ( s \right )} = \frac{P \left ( s \right )}{\left ( s+s_1 \right )\left ( s+s_2 \right )\cdots \left ( s+s_n \right )} $$
$$ \Rightarrow X \left ( s \right ) = \frac{A}{s+s_1} + \frac{B}{s+s_2} + \cdots + \frac{Z}{s+s_n} $$

Where the coefficients $A, B, ... Z$ are determined by multiplying both sides by $(s+s_i)$, and replacing $s = -s_i$.

Example: Consider the function $X(s)$:

$$X \left ( s \right ) = \frac{5s+3}{\left ( s+1 \right )\left ( s+2 \right )\left ( s+3 \right )}$$
$$ \Rightarrow X \left ( s \right ) = \frac{A}{s+1} + \frac{B}{s+2} + \frac{C}{s+3} $$

Both sides by $(s+1)$:

$$\left | A+\frac{s+1}{s+2} B+\frac{s+1}{s+3} C =\frac{5s+3}{\left ( s+2 \right )\left ( s+3 \right )} \right | _{s=-1}$$
$$\Rightarrow A = \frac{-5+3}{\left ( 1 \right )\left ( 2 \right )} = \frac{-2}{2} = -1$$

Both sides by $(s+2)$:

$$\left | \frac{s+2}{s+1} A + B +\frac{s+2}{s+3} C =\frac{5s+3}{\left ( s+1 \right )\left ( s+3 \right )} \right | _{s=-2}$$
$$\Rightarrow B = \frac{-10+3}{\left ( -1 \right )\left ( 1 \right )} = \frac{-7}{-1} = 7$$

Both sides by $(s+3)$:

$$\left | \frac{s+3}{s+1} A + \frac{s+3}{s+2} B + C =\frac{5s+3}{\left ( s+1 \right )\left ( s+2 \right )} \right | _{s=-3}$$
$$\Rightarrow C = \frac{-15+3}{\left ( -2 \right )\left ( -1 \right )} = \frac{-12}{2} = -6$$
$$\Rightarrow X \left ( s \right ) = \frac{-1}{s+1} + \frac{7}{s+2} + \frac{-6}{s+3}$$

2. Poles of multiple order.

The procedure is the same, but we have as many terms as polo multiplicity.

Example: Consider the function $X(s)$:

$$X\left ( s \right ) = \frac{1}{s\left ( s+1 \right )^3 \left ( s+2 \right )}$$
$$\Rightarrow X\left ( s \right ) = \frac{A}{s} + \frac{B_1}{\left ( s+1 \right )^3} + \frac{B_2}{\left ( s+1 \right )^2} + \frac{B_3}{\left ( s+1 \right )} + \frac{C}{s+2}$$
$$\Rightarrow A = \left [ \frac{1}{\left ( s+1 \right )^3 \left ( s+2 \right )} \right ]_{s=0} = \frac{1}{\left ( 1 \right )\left ( 2 \right )} = \frac{1}{2}$$
$$\Rightarrow B_1 = \left | \frac{1}{s\left ( s+2 \right )} \right |_{s=-1} = \frac{1}{\left ( -1 \right )\left ( 1 \right )} = -1$$
$$ \Rightarrow B_2 = \left | \frac{d}{ds} \left [ \frac{1}{s\left ( s+2 \right )} \right ] \right |_{s=-1} = \left | \frac{-\frac{d\left ( s^2 +2s \right )}{ds}}{s^2 \left ( s+2 \right )^2} \right |_{s=-1} =\left | \frac{-\left ( 2s+2 \right )}{s^2\left ( s+2 \right )^2} \right |_{s=-1} = 0 $$
$$ \Rightarrow B_3 = \left | \frac{1}{2!} \frac{d^2}{ds^2} \left [ \frac{1}{s\left ( s+2 \right )} \right ] \right |_{s=-1} = \left | \frac{1}{2!} \frac{d}{ds} \left [ \frac{-2s-2}{s^2\left ( s+2 \right )^2} \right ] \right |_{s=-1} $$
$$ = \left | \frac{1}{2} \frac{-2s^2\left ( s+2 \right )^2 + \left ( 2s+2 \right ) \frac{d}{ds} \left ( s^4 + 4s^3 + 4 s^2 \right )}{s^4\left ( s+2 \right )^4} \right |_{s=-1} $$
$$ =\frac{1}{2} \frac{-\left ( 1 \right )\left ( 1 \right )\left ( 2 \right )+\left ( 0 \right )\left ( 4s^3 +12 s^2 + 8s \right )}{\left ( 1 \right )\left ( 1 \right )} = -1 $$

General form:

$$ B_r = \left | \frac{1}{\left ( r-1 \right )!} \frac{d^{r-1}}{ds^{r-1}} \left [ \left ( s+s_i \right )^{r-1} X\left ( s \right ) \right ] \right |_{s=s_i} $$
$$\Rightarrow C = \left [ \frac{1}{s \left ( s+1 \right )^3 } \right ]_{s=-2} = \frac{1}{\left ( -2 \right )\left ( -1 \right )^3} = \frac{1}{2}$$

Therefore, the complete expansion is:

$$ X\left ( s \right ) = \frac{\frac{1}{2}}{s} + \frac{-1}{\left ( s+1 \right )^3} + \frac{-1}{s+1} +\frac{\frac{1}{2}}{s+2} $$

3. Simple complex poles

They develop in the same way.

Workshop: Carry out the expansion by hand by partial fractions of:

$$ X\left ( s \right ) = \frac{\omega _0 ^2}{s\left ( s^2 + 2 \zeta \omega _0 s + \omega _0 ^2 \right )} $$

Example: Consider the function:

$$ \frac{d^2 x\left ( t \right )}{dt^2} + 3 \frac{dx\left ( t \right )}{dt} + 2 x\left ( t \right ) = 5\, u\left ( t \right ) $$

Define $x(t)$ if:

$$ u\left ( t \right ) = \left\{\begin{matrix} 1 & t\geq 0\\ 0 & t < 0 \end{matrix}\right.$$
$$ x\left ( 0 \right ) = -1,\: x^{(1)} \left ( 0 \right ) = 2 $$

Solution

Applying Laplace:

$$ s^2 X\left ( s \right ) - s x\left ( 0 \right ) - x^{(1)} \left ( 0 \right ) +3 s X\left ( s \right ) - 3 x\left ( 0 \right ) + 2 X\left ( s \right ) = \frac{5}{s} $$
$$ \Rightarrow X\left ( s \right ) = \frac{-s^2 - s + 5}{s\left ( s^2 + 3 s + 2 \right )} = \frac{-s^2 - s + 5}{s\left ( s+1 \right )\left ( s+2 \right )} $$

To calculate the inverse of Laplace, we expand in partial fractions:

$$ \Rightarrow X\left ( s \right ) = \frac{\frac{5}{2}}{s} - \frac{5}{s+1} + \frac{\frac{3}{2}}{s+2} $$

And using the tables:

$$ \Rightarrow x\left ( t \right ) = \frac{5}{2} - 5 e^{-t} + \frac{3}{2} e^{-2t} \: \; / t\geq 0 $$

$\frac{5}{2}$ is the stationary response, and the rest is the transient response.

If we are only looking for the stationary response, we can apply the final value theorem:

$$ \lim _{t \to \infty } x\left ( t \right ) = \lim _{s \to 0} s X\left ( s \right ) = \lim _{s \to 0} \frac{-s^2 - s + 5}{s^2 + 3s + 2} = \frac{5}{2} $$

This is a way, the other option is calculating it directly with sympy:


In [ ]:
import sympy
from sympy import *

sympy.init_printing()
s = Symbol('s')
t = Symbol('t', positive=True)

In [ ]:
X = (-s**2-s+5)/((s)*(s+1)*(s+2))

In [ ]:
X

In [ ]:
X.expand()

In [ ]:
xt = inverse_laplace_transform(X,s,t).evalf().simplify()

In [ ]:
xt

Workshop: Find $x(t)$:

$$ \frac{d^2 x\left ( t \right )}{dt^2} + 34.5 \frac{dx\left ( t \right )}{dt} + 1000 x\left ( t \right ) = 1000 u\left ( t \right ) $$

Sol.: $x(t) = 1 +1.19 e^{-17.2t} sin (26.5 t - \theta ), \theta = -56.9^{\circ}$